2018
DOI: 10.4149/gpb_2017034
|View full text |Cite
|
Sign up to set email alerts
|

Toxicogenomic evaluation of liver responses induced by acrylamide and glycidamide in male mouse liver

Abstract: In current studies, histopathologic method, Agilent GeneChip hybridization and Western blot were used to investigate the toxicity of acrylamide (AA) and glycidamide (GA) in male mouse livers. The histopathologic results demonstrated that AA and GA could cause oxidative damage to mouse liver. Middle dose of GA and AA (50 mg/kg b.w./day) could significantly up-regulate the expression of cytochrome P450, as well as genes related to oxidative injury, cancer and inflammation, and significantly down-regulate the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
3
4
0
1
Order By: Relevance
“…So far, the antiapoptotic activity of curcumin has been commonly assumed as one of the important mechanisms underlying its beneficial bioactive properties. 29,30 As shown in Figure 3, immunofluorescent staining revealed significant increases in terminal deoxynucleotidyl transferase-mediated dUTP nick-end labeling (TUNEL)-positive apoptotic cells in the liver and kidney tissue slices from ACR-intoxicated rats, which were in line with the previous study 17 reporting the downregulation effect of ACR on the expression of genes related to antiapoptosis in the liver. Importantly, curcumin administration effectively decreased the number of apoptotic cells, suggesting its antiapoptotic activity in ACR-damaged livers and kidneys, which might be an important mechanism underlying its hepatoprotective and renoprotective effects against exposure to ACR.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…So far, the antiapoptotic activity of curcumin has been commonly assumed as one of the important mechanisms underlying its beneficial bioactive properties. 29,30 As shown in Figure 3, immunofluorescent staining revealed significant increases in terminal deoxynucleotidyl transferase-mediated dUTP nick-end labeling (TUNEL)-positive apoptotic cells in the liver and kidney tissue slices from ACR-intoxicated rats, which were in line with the previous study 17 reporting the downregulation effect of ACR on the expression of genes related to antiapoptosis in the liver. Importantly, curcumin administration effectively decreased the number of apoptotic cells, suggesting its antiapoptotic activity in ACR-damaged livers and kidneys, which might be an important mechanism underlying its hepatoprotective and renoprotective effects against exposure to ACR.…”
supporting
confidence: 89%
“…20 As a representative polyphenolic compound, curcumin is regarded as a 10-fold more potent antioxidant than vitamin E. 20 Importantly, although the exact etiology of ACR-induced hepatic and renal impairment is unknown, oxidative stress, which can lead to cell apoptosis, has been well accepted as a critical event and a principal mechanism. 11,13,17,18 During ACR metabolism in the body, excessive levels of reactive oxygen species (ROS) would be produced. On the other hand, ACR may decrease the antioxidant defense in the organs, thus resulting in the imbalance between the production of free radicals and their elimination by antioxidant defense.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this study we have analyzed the potential use of NAC as antidote against the systemic toxicity and neurotoxicity induced by ACR in adult zebrafish. Although ACR is considered to be a selective neurotoxicant at low to moderate concentrations, at high concentrations this compound has been reported to impair the liver 11,37 , kidney 38,39 , and intestinal 11,40 function. Whereas the 100% mortality found in animals exposed to 1.5 mM ACR for 72 h in this study might be related to a multi organic failure, the increase in survival observed in these animals after pre-treatment and co-exposure with NAC is probably related to the protection of this chemical against the toxic effect of ACR on non neural tissue (Altinoz and Turkoz 2014; Altinoz et al .…”
Section: Discussionmentioning
confidence: 99%
“…El metabolismo de la acrilamida ocurre principalmente en el hígado a través de dos reacciones la epoxidación que ocurren como consecuencia de una primera reacción a nivel hepático, donde se transforma, por acción de citocromo P450, en glicidamida 10,11 . Otra reacción es la conjugación con glutatión, that may be present in the different types of food to be safe for the population.…”
Section: Formación Y Metabolismo De Acrilamidaunclassified